“Incidencia de la Beauveria bassiana en el control de insectos” - Arboleda Valverde, Fernando Mauricio (2019)
SUMMARY When listening to microorganisms, we usually associate in an unfortunate way with infectious diseases, but the truth is that only a small group, causes diseases, and the vast majority are beneficial for man, such is the case of the fungus "Beauveria bassiana", for this reason the objective of this work was to optimize the interaction between the entomopathogenic fungi and the insect cuticle they were grown in laboratories of the Flower Company S. A., GardaExport, in culture media of cooked rice and stored in plastic bag with the fungus and placed a cotton to allow ventilation of the sample and produce the massive attack to the guest causing his death. The results showed that it is possible to increase the virulence of the entomopathogenic fungi, through a nutritional modification of the culture medium in beetles, and act as a biological insecticide. Key words: entomopathogenic fungus, biological insecticide, incidence.